MANAGEMENT OF FACILITIES AND INFRASTRUCTURE TO IMPROVE THE QUALITY OF LEARNING - Tengku Darmansyah (Universitas Negeri Medan, 2020)
Abstract: The purpose of infrastructure management is to improve the quality of learning in schools, resulting in quality output or graduates. The facilities and infrastructures owned by the school must be managed properly, planning facilities and education infrastructure is the first step to manage the facilities and infrastructure of education that exist in the school. Management of facilities and infrastructure in the school is done by planning, procurement, maintenance, storage,and control and elimination. Education facilities and infrastructure is a tool that is used directly or indirectly that supports the learning process. Educational facilities and infrastructure in the school must be in good condition and adequate to help the Progress of the learning process in the school. Efforts to provide a quality teaching and learning process then required school facilities that comply with the minimum standards of service, and in the implementation necessary the management of good. The learning process in school will run smoothly if supported by adequate infrastructure, either number, condition, or completeness. Every teacher in the learning process requires different infrastructures in supporting their performance so that the teaching and learning process can take place. With a complete and adequate infrastructure, the teacher will not convey the subject matter orally but also using the infrastructure available in the school.Keywords: Facilities and Infrastructure Management, Learning QualityAbstrak: Tujuan manajemen sarana dan prasarana adalah untuk meningkatkan mutu pembelajaran di sekolah sehingga menghasilkan output atau lulusan yang berkualitas. Sarana dan prasarana yang dimiliki oleh sekolah harus dikelola dengan baik, Perencanaan sarana dan prasarana pendidikan merupakan langkah awal dalam manage sarana dan prasarana pendidikan yang ada di sekolah. Manajemen sarana dan prasarana yang ada di sekolah dilakukan dengan cara melakukan perencanaan, pengadaan, pemeliharaan, penyimpanan dan pengendalian serta penghapusan.Sarana dan prasarana pendidikan merupakan alat yang digunakan secara langsung atau tidak langsung yang menunjang proses pembelajaran. Sarana dan prasarana pendidikan di sekolah harus dalam kondisi baik dan memadai sehingga dapat membantu berjalannya proses pembelajaran yang ada di sekolah. Upaya memberikan pelayanan proses belajar mengajar yang bermutu maka diperlukan fasilitas sekolah yang sesuai dengan standar pelayanan minimal, dan dalam pelaksanaannya diperlukan adanya pengelolaan yang baik. Proses belajar mengajar di sekolah akan berjalan dengan lancar jika ditunjang dengan sarana prasarana yang memadai, baik jumlah, keadaan, maupun kelengkapan. Setiap guru dalam melakukan proses pembelajaran memerlukan sarana prasarana yang berbeda dalam menunjang kinerjanya agar proses belajar mengajar dapat berlangsung dan menarik. Dengan adanya sarana prasarana yang lengkap dan memadai, maka guru tidak akan menyampaikan materi pelajaran secara lisan melainkan juga dengan menggunakan sarana prasarana yang tersedia di sekolah. Kata Kunci: Manajemen Sarana Dan Prasarana, Mutu Pembelajan